2003
DOI: 10.1029/2002ja009458
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of nitric oxide in the thermosphere

Abstract: Nitric oxide density in the lower thermosphere (97–150 km) has been measured from the polar‐orbiting Student Nitric Oxide Explorer (SNOE) satellite as a function of latitude, longitude, and altitude for the 2 1/2 year period from 11 March 1998 until 30 September 2000. The observations show that the maximum density occurs near 106–110 km and that the density is highly variable. The nitric oxide density at low latitudes correlates well with the solar soft X‐ray irradiance (2–7 nm), indicating that it is the sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
238
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(252 citation statements)
references
References 18 publications
13
238
1
Order By: Relevance
“…Solar soft X-ray irradiance is the primary energy driver for producing NO at low latitudes [Barth et al, 1988]. At high latitudes, auroral electrons are considered to be the primary source of energy that leads to enhanced NO production [Siskind et al, 1989;Saetre et al, 2007;Barth et al, 2003]. More recently, there has been a greater appreciation for the role of highlatitude Joule heating in NO production, primarily because the production rates are so sensitive to the temperature [Barth et al, 2009;Barth, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Solar soft X-ray irradiance is the primary energy driver for producing NO at low latitudes [Barth et al, 1988]. At high latitudes, auroral electrons are considered to be the primary source of energy that leads to enhanced NO production [Siskind et al, 1989;Saetre et al, 2007;Barth et al, 2003]. More recently, there has been a greater appreciation for the role of highlatitude Joule heating in NO production, primarily because the production rates are so sensitive to the temperature [Barth et al, 2009;Barth, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…[11] The calculated NO densities for the time and place of the rocket measurements are shown in Figure 1 along with measurements by the SNOE (Student Nitric Oxide Explorer) satellite [Barth et al, 2003]. The satellite measurements are for local time 10 -11 am, for periods of high geomagnetic activity around the equinoxes in 1998 -2000 and are a global average for 65°geomagnetic latitude.…”
Section: Prediction Of No Densitiesmentioning
confidence: 99%
“…These conditions differ from those of the rocket measurements, and hence of the current calculations, in that solar activity is estimated (using the MSISE-90 model) to be higher on average, solar input is less (as the rocket measurements were made on April 13th, closer to midsummer) and the rocket measurements were made at $11 pm. The estimated 18% uncertainty in the measured densities and the height resolution [Barth et al, 2003] is indicated by error bars drawn at one height.…”
Section: Prediction Of No Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the nominal scans are carried out only up to about 91 km, they do not sample the lower thermosphere where the largest NO densities are typically located, above ≈ 100 km (Barth et al, 2003;Marsh et al, 2004;Minschwaner et al, 2004;Funke et al, 2005; Published by Copernicus Publications on behalf of the European Geosciences Union. 210 S. Bender et al: SCIAMACHY nominal NO retrieval 2015).…”
Section: Introductionmentioning
confidence: 99%